A Commentary: The pandemic is calling for effective personal protection through innate immunological boosting - Chung-Lap Ben Chan; Chun-kwok Wong; Ping-chung Leung (Journal of Vaccines and Immunology - Peertechz Publications, 2021)
It is logical to rely on effective vaccinations to overcome the pandemic as well as future up-coming epidemics. When the scale of involvement and the speed of spread are unusually wide and extensive, as is happening in the current Pandemic, vaccination cannot effectively satisfy the expectations. Innate Immunity of the individual determines whether he or she is more resistant to infection, or on the contrary, more susceptible. A strong background of innate immunological defense ability allows the individual to resist infection and, even if infected will be able to maintain a mild course. Recent studies have indicated that Innate Immunity could be "trained" to arrive at a more effective and more sustained ability to resist incoming adverse organisms: though short of specificity like vaccination, yet could provide a general combatting coverage, from the stage of early organism entry to the subsequent fight for elimination. Research has identified that micro-nutrients in food stuffs and special lipo- or glyco-proteins could provide enhancements in the perfect maintenance of the Immunological System to provide an ideal ground for "trained immunity" development. Since Vitamin D has long been revealed being protective against respiratory infections via rather sophisticated pathways, it is suggested that it could be combined with other micro nutrients like β glycan to form an effective Innate Immunity booster in support of specific vaccination.